Molecular characterisation of measles virus strains among refugees from Central African Republic in Cameroon in 2014. Issue 3 (9th January 2018) - Ndombo, P. K.; Ndze, V. N.; Mbarga, F. D.; Anderson, R.; Acho, A.; Ebua Chia, J.; Njamnshi, A. K.; Rota, P. A.; Waku-Kouomou, D.
Abstract: Measles is a highly infectious human viral disease caused by measles virus (MeV). An estimated 114 900 measles deaths occurred worldwide in 2014. There are currently eight clades (A–H) comprised 24 MeV genotypes. We sought to characterise MeVs among Central African Republic (CAR) refugees during the 2014 measles epidemic in Cameroon. Samples were collected from children <15 years with suspected measles infections in two refugee camps in the east region of Cameroon. Viral RNA was extracted directly from urine samples. RNA detection of MeV RNA was performed with real-time reverse transcription polymerase chain reaction (PCR) to amplify a 634 bp nucleotide fragment of the N gene. The sequence of the PCR product was obtained to determine the genotype. MeV RNA was detected in 25 out of 30 samples from suspected cases, and among the 25 positive samples, MeV sequences were obtained from 20. The MeV strains characterised were all genotype B3. The MeV strains from genotype B3 found in this outbreak were more similar to those circulating in Northern Cameroon in 2010–2011 than to MeV strains circulating in the CAR in 2011. Surveillance system should be improved to focus on refugees for early detection of and response to outbreaks.